Understanding culture as a project: Designing for the future of an Indigenous community in Québec - Leitão, Renata M.; Roth, Solen (FormAkademisk, 2020)
This article argues that, in collaboration with Indigenous [and non-Western local] communities, social designers should approach “culture” not only as a form of heritage that should be preserved and transmitted, but also as a project that weaves together heritage, current material circumstances, and desirable ideas for the future. We therefore examine the notion that every culture is intrinsically oriented towards the future, representing a trajectory that links the past to a projected ideal of well-being. Thus, cultural diversity leads to numerous trajectories and distinct futures, contrary to the colonial ideology according to which only one trajectory is possible: that which adheres to the project of eurocentric modernity. Based on a participatory research action project called Tapiskwan, which focused on the aspirations of the Atikamekw Nehirowisiwok, we propose that the ultimate goal of social designers should be to nurture local communities’ capacity to (re)create their own autonomous trajectories, in pursuit of the good life as their culture defines it.